Assessment of Air Pollution Tolerance Index (APTI) for Selected Ornamental Plants in Urban Metropolis of Northern India - Saxena, Pallavi; Sonwani, Saurabh; K. Gupta, Anil (Asian Journal of Chemistry, 2021)
Present study aims to evaluate the tolerance and sensitivity of some selected common ornamental plants like Dracaena deremensis, Tagetes erecta and Dianthus caryophyllus by the Air Pollution Tolerance Index (APTI) at selected sites in an urban metropolis of Northern India, Delhi city. Air pollutant concentrations were monitored at Site I (nearby traffic intersection with less vegetation) and Site II (far by from traffic intersection with dense vegetation) and selected plant species were examined for their biochemical response during winter months (November 16, 2016 – February17, 2017). Based on the results, Dracaena deremensis and Tagetes erecta were segregated under tolerant whereas, Dianthus caryophyllus was under the sensitive category. Therefore, Dracaena deremensis and Tagetes erecta can be used as natural air filters or sinks for mitigation of air pollution and Dianthus caryophyllus as biomonitors or bioindicators.